2001
DOI: 10.1002/1521-3773(20010716)40:14<2688::aid-anie2688>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Nematic Dendrimers Based on Carbosilazane Cores

Abstract: The controlled synthesis of nematic nanophase‐separated materials poses an attractive synthetic challenge. The use of carbosilazane multipodes and dendrimers (such as 1) in conjunction with laterally attached mesogens allows the systematic investigation of the structure–property relationships of room‐temperature nematic liquid crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…As for the carbosilazane dendrimers (N C = 3, N B = 2), two series (G0-G2) with laterally attached mesogenic units were reported. Depending on the mesogenic unit, these dendrimers exhibit a single room temperature N phase 53 or a N-SmC and a N-Col dimorphism on increasing generation. 54 Thus, the ''side-on'' attachment of mesogenic groups appears to be an excellent strategy to induce pure N systems, although, due to the strong tendency of the core to phase separate as the generation increases, the strongly segregated smectic and columnar supramolecular organizations were inescapably formed.…”
Section: Liquid-crystalline Dendrimersmentioning
confidence: 99%
“…As for the carbosilazane dendrimers (N C = 3, N B = 2), two series (G0-G2) with laterally attached mesogenic units were reported. Depending on the mesogenic unit, these dendrimers exhibit a single room temperature N phase 53 or a N-SmC and a N-Col dimorphism on increasing generation. 54 Thus, the ''side-on'' attachment of mesogenic groups appears to be an excellent strategy to induce pure N systems, although, due to the strong tendency of the core to phase separate as the generation increases, the strongly segregated smectic and columnar supramolecular organizations were inescapably formed.…”
Section: Liquid-crystalline Dendrimersmentioning
confidence: 99%
“…Side-chain and main-chain liquid-crystal polymers [3] have internal flexible linkages as an intrinsic part of their structure. Dendrimers [4] and multipodes [5] have flexible linking chains as part of threedimensional (3D) macromolecular structures that can also form liquid-crystal phases. The simplest molecular structure having core flexibility is a dimer structure in which two semirigid mesogenic groups are connected by a flexible chain.…”
Section: Introductionmentioning
confidence: 99%
“…Important studies in dendritic liquid crystals to understand various aspects of mesophase evolution include: (i) changes in the dendrimer types, such as, carbosilane, PAMAM, PPI, and siloxane, and a homologous series of poly(propyl ether imine) (PETIM) dendrimers and changes in the dendrimer generations; (ii) varying linker lengths connecting the dendrimer backbone and the mesogenic moiety; (iii) varying alkyl chain length at the peripheries; (iv) the mode of attachment of the mesogenic moiety to the dendrimer, such as, side on or end on; (v) changing the shape of mesogenic moieties, such as, linear, radial and banana shaped and the degree of branching in the core . In the studies of dendritic LCs, to the best of our knowledge, no work has been reported so far which deals with the study of change in the mesophase by varying the flexibility and shape of the linkers within one particular dendrimer generation.…”
Section: Introductionmentioning
confidence: 99%